HPTLC Fingerprint Authentication of Selected Sideritis spp. Using a Pharmacognostic Approach - Pihan, Lisa-Anna-Maria; Peter, Samuel; Vollmer, Günter; Meier, Beat; Wolfram, Evelyn (Planta Medica, 2021)
The genus Sideritis (Lamiaceae) comprises around 150 species, of which many are popular herbal remedies in Mediterranean folk medicine. Already mentioned by Dioscorides and Theophrastus, the “ironwort” or “Greek mountain tea” has been receiving increased attention in recent years. A European Union herbal monograph and assessment report (HMPC) has been issued, covering the species Sideritis scardica, S. clandestina, S. raeseri, and S. syriaca. This study presents results of a first pharmacognostic examination of the botanical and phytochemical differences among and between these emerging commercial species, and other, less studied species. An HPTLC method is proposed for normal phase separation of the species; this means applying two mobile phases on silica plates and subsequent derivatization with natural product reagent (NP/PEG) for visualization of phenolic compounds and anisaldehyde for a broader detection. With the help of selected reference compounds, a system suitability test was established for proper chromatographic separation. The method was applied to specimens from botanical gardens and commercial raw material in order to test its suitability for differentiation and authentication. The HPTLC analysis also includes, for the first time, S. hyssopifolia and other less used Sideritis species. The results might enable the development of a validated phytochemical fingerprint authentication procedure for quality assurance of Sideritis herba.
Keywords: HPTLC; authentication; Lamiaceae; Sideritis spp.; Sideritis scardica; Sideritis raeseri; Sideritis hyssopifolia